Detection of SARS-CoV-2, Influenza Type A/B Viruses among Acute Respiratory Patients in Khartoum Hospital, Sudan - Adam, Rawia. O.; Khalifa, Tasneem. M.; Elameen, Omklthoom. M.; Ahmed, Sanaa. M. E.; El Hussein, Abdel Rahim M.; Enan, Khalid. A. (Journal of Pharmacy Practice and Community Medicine, 2026)
Background Viruses are the most common cause of upper respiratory tract infection. Patients infected with severe acute respiratory viruses like Coronavirus 2 (SARS-CoV-2), Influenza A (flu A) and Influenza B (flu B) have overlapping clinical presentations, but the approaches for treatment and management of infections caused by these viruses are quite different. Therefore, implementation of rapid virology assay would enable the detection and differentiation of SARS-CoV-2, flu A, flu B, in upper respiratory tract specimens and though the optimum treatment. Materials and Methods In this study NPAs samples were collected from Sudanese patients of various age groups presented to Khartoum hospital with acute respiratory symptoms that had lasted for 3 days or less, to detect the presence of Influenza type A and B or SARS-CoV2 viruses or both. Results The study revealed that 42.8% of patients were SARS-CoV2 positive, while no influenza or co-infection had been detected. Conclusion Indicating that most of respiratory infections in Sudan could be due to SARS-CoV-2 virus. The study aimed to aid differential diagnosis of the viral respiratory tract infections, though providing proper clinical management and antiviral therapy.
Keywords: SARS-CoV-2; Influenza virus; Co-infection; Multiplex RT-PCR; Nasopharyngeal aspirates; Respiratory viral infections; Khartoum State; Sudan; Acute respiratory symptoms; Viral RNA detection